Living with or beyond lymphoma: A rapid review of the unmet needs of lymphoma survivors - Boland, Vanessa; Drury, Amanda; Sheaf, Greg; Brady, Anne-Marie (Wiley, 2022)
Objective: To establish an understanding of the unmet needs of people living with or beyond a lymphoma diagnosis. Survivors of lymphoma are at increased risk of unmet needs due to cancer, treatment‐related toxicities and extended survivorship. Despite the rapidly growing numbers of lymphoma survivors, their needs and research priorities are underserved and undervalued, therefore left largely unaddressed. Methods: A rapid review method and reflexive thematic analysis approach assimilated current knowledge. Eligibility criteria included quantitative, qualitative, or mixed approaches employing cross‐sectional, longitudinal, cohort or review designs focused on the needs of adult lymphoma survivors (any subtype or stage of disease). Five databases: CINAHL, EMBASE, Medline, PsycInfo and Scopus, were systematically searched. Results: Forty‐seven studies met the inclusion criteria via a stringent screening process facilitated by NVivo. Almost 60 per cent of articles were published within the last five years and investigated a homogenous lymphoma sample. Most studies employed quantitative approaches (77%) and cross‐sectional designs (67%). Studies were of high methodological quality. Five major themes were identified: disparity in health service delivery, the psychological impact of cancer, impactful and debilitating concerns, the monetary cost of survival and insufficient provision of survivorship information. A meta‐analytical approach was not feasible due to the breadth of methodologies of included studies. Conclusions: This review shows that lymphoma survivors experience a myriad of unmet needs across multiple domains, reinforcing the need for lymphoma‐specific research. However, more research is needed to advance and achieve informed decision‐making relating to survivorship care, placing due attention to the needsand research priorities of lymphoma survivors.
Trinity Health and Education International Research Conference
PUBLISHED
School of Nursing and Midwifery, Trinity College Dublin
Keywords: blood cancer; cancer survivorship; haematological malignancy; Hodgkin; lymphoma; needs; non‐Hodgkin; psycho‐oncology; quality of life; unmet needs; Cancer